A Mediation Model of Intrinsic Work Motivation and Job Satisfaction To Develop Aircraft Technician Performance - Prinandita, Prinandita; Moeins, Anoesyirwan; Zain, Yuli (Dinasti Publisher, 2024)
The purpose of this study is to analyze the influence of training programs on technician intrinsic motivation, the influence of training programs on technician performance, intrinsic motivation is a mediating variable between training programs on technician performance, the influence of training programs on technician job satisfaction, and job satisfaction is a mediating variable between training programs on the performance of aircraft technicians of PT GMF AeroAsia Tbk. The target population in this study is 3061 Aircraft Technicians who work in Base Maintenance and Line Maintenance of PT GMF AeroAsia Tbk in the working areas of Jakarta, Medan, Surabaya, Denpasar, and Makassar. The sample size was 210 respondents. Sampling applied probability sampling techniques, using a survey method with questionnaire instruments. The data was processed and analyzed using SPSS software. The results of the study showed a positive and significant influence of the training program on the intrinsic motivation of technicians, there was a positive and significant influence of the training program on the performance of technicians, intrinsic motivation was a mediating variable between the training program on the performance of technicians, there was a positive and significance influence the training program on the job satisfaction of technicians and the job satisfaction was a mediating variable between the training program on the performance of PT Aircraft Technicians GMF AeroAsia Tbk. Based on the results of the determination test, the contribution of the influence was prevented on work performance by 69.1%.